Ottoman Representation in Nineteenth Century Universal Expositions - Erguney, Yesim Duygu; Kara Pilehvarian, Nuran (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
The post-1815 years of the Industrial Revolution witnessed the growth of international free trade, prompted by the opening up of new markets, accumulation of capital, and the bountiful supply of cheap raw materials made available by colonization. In entities such as the Ottoman Empire, whose regimes maintained strict state control and thus restricted a liberal economy, the process of participation in international trade occurred in an entirely different manner. Primarily, this article aimed to compare and evaluate the economic, social and political changes in the Ottoman and European worlds during this period by examining how these changes were reflected in the architectural representations and displays of symbolic wares during the World Expositions of the nineteenth century. The literature review revealed orientalism as a perspective much used by researchers in attempting to draw cultural comparisons for this century, dominated as it was by colonization. However, when the scope of orientalism was broadened to include entities such as the Ottoman Empire-which remained beyond the sphere of Western imperialism-we see that architectural and art products representing or inspired by the Ottomans also came to be examined from this perspective. Taking this issue as its starting point, the study sets itself apart from those which limit themselves to pure orientalism. Instead, it brings together those elements representing of the Ottoman state at the World Expositions, and aims to analyze them in their economic, cultural and esthetic entirety. The first of these expositions was the London Exposition in 1851, and the study examines this and the subsequent six. Of these, four were held in Paris (1867, 1878, 1889 and 1900), one in Vienna (1873) and one in Chicago (1893). The research does not include expositions taking place after the turn of the century, since, by that time, they were becoming akin to specialized trade fairs. Also included in a separate section of the study is the 1863 Istanbul Exposition (Sergi-i Umumii Osmani'ye). While not having the same international weight as the World Expositions, this was included in the study to illustrate how it reflected change, being the first such exposition in Ottoman lands to have pavilions for foreign exhibits. Research shows that the elements chosen to represent the Ottoman state at the expositions were not from the classical period, but rather from both the earlier and later periods, and the article considers these choices to have been based on a desire by the Ottomans to be seen as part of Europe in an era dominated by colonization.
Keywords: World's fairs; capitalism; universal modernity; industrial revolution; local representation; Architecture